Blaming climate change? How Indian mainstream media covered two extreme weather events in 2015. (July 2020) - Painter, James; Osaka, Shannon; Ettinger, Joshua; Walton, Peter
Highlights: This article analyses the media coverage of the science of extreme event attribution. It is the first to focus exclusively on a low-income country. The Indian media seldom quoted the scientific studies on the extreme weather events. Politicians and NGOs are quick to blame climate change without quoting the science. The article maps the challenges for journalists and makes recommendations. Abstract: Reporting the links (or lack of them) between human-induced climate change and individual extreme weather events poses a series of challenges for journalists. In recent years, their task has become more complicated by the increase in the number of extreme event attribution (EEA) studies which assess how climate change is affecting the intensity or likelihood of specific weather events. Such studies are complex, contain uncertainties, and can be difficult to explain to a lay audience. Previous scholarship has largely focused on media coverage of extreme events in developed countries, and on the volume of coverage of the links to climate change, without examining references to EEA studies. To help fill this gap, we take India as our case study, and the mainstream media coverage there of the Chennai rainfall event and the heat wave in Andhra Pradesh in 2015. Both events were subject to attribution studies. Amongst our findings are that journalists most commonly used generic phrases to describe the link between such events and climate change; politicians and NGOs often 'blamed' climate change without reference to the science; and relevant EEA studies were seldom quoted. Based on our findings, we make some preliminary recommendations for training journalists in India and elsewhere to support accurate reporting of extreme events and their possible linkages to climate change.